Shumaq Kawsay como herramienta pedagógica y jurídica para la Educación Intercultural Bilingüe (EIB) - Sánchez De La Cruz, Wilmer (2025)
This study addresses the concept of Shumaq Kawsay as a pedagogical and legal instrument based on indigenous cultures, adapted to the context of Intercultural Bilingual Education (EIB). Its objective is to highlight the potential of Shumaq Kawsay to strengthen indigenous languages and cultures,integrating the Andean worldview and the principles of «good living» into educational and legal systems. It is proposed that this approach can revitalize the cultural and linguistic identity of indigenous communities, promoting an inclusive and sustainable model. The methodology used is qualitative with an ethnographic approach, focused on the community of Ayamachay, Ferreñafe, Lambayeque. Through interviews and questionnaires directed to focus groups, the implementation of Shumaq Kawsay as a pedagogical tool in community and school life is explored, reflecting cultural and social practices that support «good living.» The study seeks to demonstrate how Shumaq Kawsay applied to IBE can strengthen cultural and linguistic identity, as well as propose pedagogical models that combine traditional and academic knowledge, strategies to revitalize native languages, and bases for policies that respect collective rights. Among the conclusions, it is highlighted that Shumaq Kawsay strengthensthe cultural and linguistic identity of indigenous communities, such as Ayamachay, through its integration into Intercultural Bilingual Education (EIB), revitalizing Inkawasi-Kañaris Quechua and community values. In addition, its normative strategies guarantee collective rights, promote inclusivepolicies, and reinforce the social fabric. This approach responds to the challenges of globalization, preserving native languages, promoting equity, respect for nature, and sustainability.